A randomized, prospective trial on efficacy and tolerability of low-volume bowel preparation methods for colonoscopy. Issue 2 (February 2015) - Yoo, In Kyung; Lee, Jong Soo; Chun, Hoon Jai; Jeen, Yoon Tae; Keum, Bora; Kim, Eun Sun; Choi, Hyuk Soon; Lee, Jae Min; Kim, Seung Han; Nam, Seung Joo; Kang, Hyo Sung; Lee, Hong Sik; et al.
Abstract Background Low-volume bowel preparations have been shown to provide an equivalent cleansing effect as that of a standard 4 L polyethylene glycol. However, studies comparing the efficacy of low-volume bowel preparations are few, and the results have been controversial. This study aimed to compare the bowel cleansing quality and tolerability between sodium picosulfate/magnesium citrate and polyethylene glycol with ascorbic acid. Methods A randomized study was performed with two hundred outpatients who were prospectively enrolled. The Boston Bowel Preparation Scale and the Aronchick scale were used to evaluate the bowel cleansing quality, and bubble scoring was also performed to back up both results. To investigate patients' preferences and tolerability, a questionnaire was administered. Results Sodium picosulfate/magnesium citrate was not inferior to polyethylene glycol with ascorbic acid in terms of successful bowel preparation (≥6 Boston scale score: 80% vs. 82%; p = 0.718, adequate Aronchick grade: 93% vs. 96%; p = 0.352). In addition, sodium picosulfate/magnesium citrate caused fewer gastrointestinal symptoms, and tasted better than polyethylene glycol with ascorbic acid. Conclusions Sodium picosulfate/magnesium citrate was not inferior to polyethylene glycol with ascorbic acid in cleansing efficacy, and was found to have higher tolerability.